تأولية الفرد عند اوغيست كونت - بريكي كريمة (University of Eloued جامعة الوادي, 2024)
الملخص: إننا في هذا البحث نسعى الى بيان أن مسألة الفرد من المسائل الفلسفية التي لا تزال تطرح بحدّة على صعيد التفكير الفلسفي حيث تطور مفهوم الفرد من اليونان باعتباره مصطلح بيولوجي الى القرن السابع عشر ككيان له مجموعة من الخصائص التي تجعل منه هوية ما ،الى القرن التاسع عشر عصر الفردانية باعتباره عصرا مؤسسا لمقولة الفرد حيث اصبح مشكلا وجوديا ،وهو الموضوع الذي تناوله اوغيست كونت (1857-1798) في الفلسفة الوضعية معتبرا أن الفرد هو كائن اجتماعي بالأساس وأن أهداف المجتمع ما هي إلا أهداف فردية تحقق سعادة الفرد وتسعي إلى تحقيق آماله وطموحاته، الذي يتحمّل مسؤولية ارتباطه بغيره، ،ويبين كونت أن الفرد هو مرتبط في وجوده بالفترة المعاصرة الذي تعيشها أوروبا بعد الثورة الفرنسية، فكيف بالإمكان تحديد موقف كونت من العلاقة بين الفرد والمجتمع ؟ كيف بنى كونت مقولة الفرد ؟ هل عمل على تذويب الفرد في المجموعة ؟. Abstract : In this research, we have shown that the question of the individual is one of the philosophique issues that still raises philosophy Where the concept of an individual evolved from Greece was a biological term and in the seventeenth century an entity with a set of characteristics that make it an identity, to the nineteenth century the era of individualism is an era of foundations of an individual's saying where it became an existential problem This is the topic addressed by Auguste Comet in positive philosophy, considering that the individual is essentially a social being. The objectives of society are individualized to achieve the happiness of the individual who bears responsibility for his association with others. Comte indicates that the individual is associated in his presence with the contemporary period in Europe after the French Revlution
Keywords: فرد; مجتمع; ذات; الاخر; Individual; Community; Same; Other